Pengembangan Rear Diffuser City Car sebagai Komponen Modifikasi Berbasiskan Metode Reverse Engineering yang Didukung Teknologi 3D Scanning dan 3D Printing: Indonesia - Wibowo, Dadi Satrio; Riza, Rahmat; Puspaputra, Paryana (UII, 2026)
The addition of a rear diffuser to a city car is a modification concept that lends it a distinctive character. Developing this component to provide further added value remains a challenge. In this study, the modification process for the rear diffuser of a city car was carried out using a reverse engineering approach supported by 3D scanning, re-drawing, modification, and prototyping. The 3D scanning process was performed using a 3D scanner with a scanning volume ranging from 0,2 m 0,2 m 0,2 m to 2 m 2 m 2 m and an operational range 0,45 m to 1,6 m. This process was optimized through object colorization. CAD models were re-drawn and evaluated using a combination of CAD and CAE software and their features. The results of this study indicated that reverse engineering methods supported by 3D scanning and 3D printing technologies could results in a variety of rear-diffuser designs for city cars, with airflow analysis showing that these designs do not compromise vehicle performance.